2009
DOI: 10.1016/s1090-3801(09)60068-9
|View full text |Cite
|
Sign up to set email alerts
|

65 Chronic Pain and Quality of Life in Schizophrenic Patients

Abstract: Objective: To identify the prevalence and characteristics of chronic pain in schizophrenic patients and to compare the quality of life in patients with and without chronic pain. Methods: Crossover design with a probablistic sample of 205 adult schizophrenic outpatients (80% paranoid schizophrenia). Socio-demographic, psychiatric disorder, pain and quality of life (WHOQOL-brief) data were collected between June and September 2008. Results: Mean age was 37 years, 65% were men, and the mean time spent in school w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Females had a higher presence in most samples 9,12,14,[16][17][18] . Only in two studies, males prevailed 10,13 . One study failed to present the quantity of the sample distributed by gender 11 , and one of the samples had an equitable representation among peers 15 .…”
Section: Contentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Females had a higher presence in most samples 9,12,14,[16][17][18] . Only in two studies, males prevailed 10,13 . One study failed to present the quantity of the sample distributed by gender 11 , and one of the samples had an equitable representation among peers 15 .…”
Section: Contentsmentioning
confidence: 92%
“…Of these, after the screening, 11 studies were included. One article was excluded because it was published in two different journals, totaling a sample of 10 papers [9][10][11][12][13][14][15][16][17][18] . The total population of the selected studies was 8,508 individuals, of which the samples ranged from 60 15 to 2,297 12 participants.…”
Section: Contentsmentioning
confidence: 99%
“…Research conducted in Russia has reported prevalence rates of over 30% for those experiencing low back pain [22], 13% for chronic generalized pain [23], and 46% for various types of arthralgia [24]. Research in Brazil has largely focused on pain reported by specific populations [25] or in conjunction with comorbid conditions [26]. A 2006 survey of adult employees found that nearly two-thirds of participants reported having a chronic pain condition, particularly among women [27], while a recent population-based survey found a high rate of back pain (12%) among respondents [28].…”
Section: Introductionmentioning
confidence: 99%